The Toxicity and Cytotoxicity Test of Anticancer Peptides Isolated from Symbiotic Bacteria - Asmi, Nur; Ahmad, Ahyar; Natsir, Hasnah; Karim, Harningsih; Muhakim, Ali; Khairunnur, Siti (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
The purpose of this research was to evaluate the toxicity and cytotoxicity of the fragment peptide from symbiotic bacteria in the lung cancer LK-2 cell line, compared normal M5S cell line. Protein hydrolyzates were separated using Molecular Weight Cut Off (MWCO) to isolate peptide fragments. Fragments were categorized as ≤ 5 kDa, > 5-10 kDa, and > 10 kDa to evaluate their toxicity through the Brine Shrimp Lethality Test (BSLT) method and to study cytotoxicity effects and proliferation in LK-2 lung cancer cells against normal M5S cells. MTT assay was used to analyze the percentage of living cells and cell growth. The Selectivity Index (SI) equation was applied to determine selectivity. Findings indicated that the peptide fragment ≤ 5 kDa had the highest toxicity, with an LC50 of 8.15 µg/ml. The number of LK-2 cells that died increased when exposed to peptide fragments of sizes ≤ 5 kDa, > 5-10 kDa, and > 10 kDa over 16 hours. Moreover, cell growth in LK-2 cells decreased after 16 hours, while there was no significant decline (P < 0.05) in M5S cells compared to the controls. The peptide fragments with molecular weights ≤ 5 kDa and > 5-10 kDa demonstrated the highest selectivity, resulting in an SI value of 3. These results suggest that the selected peptide fragments may serve effectively as anticancer agents. This study highlights the potential of peptides from symbiotic bacteria as possible treatments for cancer, particularly lung cancer.